MODEL OF CULTURAL VALUES FOR CREATIVE SMALL AND MEDIUM INDUSTRIES GROWTH IN WEST JAVA - SUPARMAN NIM 33411007, SRIBAGJAWATI
In 2015 the creative economy contributes 7.38% to the national GDP and contributes 13.9% towards the absorption of the national workforce. The creative economy contributes substantially to the growth of the national economy, but there are various problems faced by IKM (Industi Kecil dan Menengah/Small and Medium Industry)-based creative economy, namely: still low domestic sales and exports; still high production cost; still high number of failed products and not yet able to meet the quantity of product delivery. These problems indicate problems in organizational effectiveness. These problems indicate a problem on the effectiveness of the organization with a measure of creative IKM performance. Previous studies have linked performance with organizational culture. Organizational culture can be reflected through cultural values. The model of cultural values in this study is a model of the influence of cultural values on the performance of creative IKM, which consists of operational performance and financial performance. The influence between cultural values and creative IKM performance can be mapped using the Competing Values framework. The model of influence of cultural values on the performance of creative IKM was developed in each phase of creative IKM growth, in accordance with Abernathy and Utterback (1988) research, ie. fluid, transition and mature. The research was conducted by mixed methods which include preliminary case study qualitatively with case study method on three creative IKM and quantitative research through survey on 265 creative IKM. The unit of analysis of the research is the level of creative IKM companies, the researcher applies as an observer who has no intervention on the sample state and the researcher performs a single shooting of the creative state of the IKM. Likert scale ranges from one to five are used in questionnaires with two data processing. First, data processing with all samples and second, data processing with three groups of sample based on growth phase of fluid, transition and matuer. Data processing on survey results using Structural Equation Modeling (SEM) using Smart PLS 2.0 program. The Cultural Values model consists of two models: the internal Cultural Values model and the external Cultural Values model. In the internal Cultural Values model, the variables that affect the operational performance are internal cohesiveness variables and internal processes variables. While in the external Cultural Values model, the variables affecting financial performance are innovation variables and market variables. the continuation of the business growth phase, while the internal process influences decreases as the business growth phase grows. This means that the more established a creative IKM, the more attention to work atmosphere, work comfort, employee empowerment and open communication. The results of external Cultural Values model based on business growth phase show that the influence of innovation variables is increasing along with the continuation of business growth phase, while the influence of market decreases along with the further growth of business. This means that the more established a creative IKM, it will further strengthen the ability to create new products or innovate. In a creative, fluid-based IKM that will move on to the transition phase, it must increase internal cohesiveness values and increase the innovation values. Increasing values on internal cohesiveness can be done through teamwork, participation, employee engagement and open communication. The ability of innovation can be developed through the enhancement of the ability to create new products by increasing the values of creativity, taking risks and adaptability. In the creative IKM in transition phase, in order to move to the mature phase, the creative IKM must increase the values of internal integrity and innovation values, while maintaining the values of internal processes and market understanding.